Cracking Caused by Early-age Deformation of Concrete – Prediction and Control. (2017) - Gilbert, R.I.
Abstract: This paper deals with the control of cracking caused by restraint to early-age cooling and shrinkage of concrete. Such cracking is inevitable in many situations and a significant amount of reinforcement crossing each crack is required for crack control. Rational procedures are proposed for determining the degree of restraint in a variety of practical reinforced concrete members and the amount of reinforcement required for the control of early-age cracking. Procedures for calculating the width and spacing of cracks are also outlined.